2016
DOI: 10.1017/s0373463315001058
|View full text |Cite
|
Sign up to set email alerts
|

Development and Performance Validation of a Navigation System for an Underwater Vehicle

Abstract: Underwater position data is a key requirement for the navigation and control of unmanned underwater vehicles. The proposed navigation scheme can be used in any vessel or boat for any shallow water vehicle. This paper presents the position estimation algorithm developed for shallow water Remotely Operated Vehicles (ROVs) using attitude data and Doppler Velocity Log data with the initial position from the Global Positioning System (GPS). The navigational sensors are identified using the in-house developed simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Many scientists globally are working on comparative (terrain reference) navigation [8][9][10]. Most studies have analyzed the shape of the bottom of bodies of water obtained from the depth of the basin.…”
Section: Introductionmentioning
confidence: 99%
“…Many scientists globally are working on comparative (terrain reference) navigation [8][9][10]. Most studies have analyzed the shape of the bottom of bodies of water obtained from the depth of the basin.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, few works deal with testing and validating functionalities with a complete specification comparisons. From the authors cited previously, in [10], the authors validate that the final error is below a desired threshold (5%). In [6], the authors validate that the DVL used meets the indicated developer specification (0.2% maximum error).…”
Section: Baseline and Related Workmentioning
confidence: 69%
“…For example, in [5], the authors performed tests in a river with several marine robots and only compared the localization performance of an Extended Kalman Filter (EKF) with other filters. In [10], the authors measured the precision of the navigation of their AUV by evaluating the position of the robot after resurfacing. In [6], the authors also performed sea trial tests comparing the speed measurement of their DVL sensor with the data of an accurate GNSS-USBL used as ground truth.…”
Section: Baseline and Related Workmentioning
confidence: 99%
“…The comparative navigation methods have been mainly used, so far, for positioning with the aid of a radar and electronic navigation maps [18][19][20], although in recent years the comparison methods are becoming more and more frequently used in underwater positioning [21][22][23][24][25][26]. The research direction which has recently been very popular in this area refers to mobile navigation [27][28][29].…”
Section: Comparative Navigation Methodsmentioning
confidence: 99%